2019
DOI: 10.1007/s12110-019-09355-3
|View full text |Cite
|
Sign up to set email alerts
|

Once and Again

Abstract: Animal and human studies suggest that parenting style is transmitted from one generation to the next. The hypotheses of this study were that (1) a mother's rearing experiences (G1) would predict her own parenting resources (G2) and (2) current maternal mood, motivation to care for her offspring, and relationship with her parents would underlie this association. In a subsample of 201 first-time mothers participating in the longitudinal Maternal Adversity, Vulnerability and Neurodevelopment project, we assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 108 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…Parenting stress was directly affected by the maternal history of childhood maltreatment (Unternaehrer et al, 2019), especially when this maltreatment was moderate to severe (Galbally et al, 2019). Maternal depressive symptoms mediated the pathway between maternal history of childhood maltreatment and later parenting stress (Unternaehrer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Parenting stress was directly affected by the maternal history of childhood maltreatment (Unternaehrer et al, 2019), especially when this maltreatment was moderate to severe (Galbally et al, 2019). Maternal depressive symptoms mediated the pathway between maternal history of childhood maltreatment and later parenting stress (Unternaehrer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, suboptimal parental bonding in a parent g -child relationship has been posited to be intergenerationally transmitted through less emotionally available parent-child interactions in the subsequent generation, where insecurely attached mothers exhibit less maternal sensitivity when interacting with their own children [43], while their children tend to display less responsiveness towards them [44]. Parental attachment has also been shown to be influenced by parenting stress, where mothers who perceived a lower-quality rearing from their parents were more likely to experience greater parenting stress when they become parents as compared to mothers who perceived higher-quality rearing from their parents [45].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the impact of maternal exposure to interpersonal violence (including childhood maltreatment experiences +/− intimate partner violence), out of 29 relevant articles, 25 reported on early mother-child relational outcomes. 107 -109 Of these studies, 19 reported on mother-child attachment or relationship quality, 14,105,110 -125 10 on maternal sensitivity or responsiveness, 107,108,110,112,113,121,122,126 -128 one on maternal reflective function, 128 one on maternal structuring, 129 four on maternal intrusiveness, 110,119,126,128 one on parenting competence, 130 two on harsh parenting, 110,119 two on negative infant emotionality, 107,108 two on child internalizing symptoms, 111,115 three on child externalizing symptoms, 111,115,121 and one reporting on total child psychiatric symptoms. 131 Overall, less optimal internal working models and severity of maternal mood or PTSD symptoms and alexithymia were associated with more negative parenting behaviors, lower reflective function, and negative offspring outcomes 105,110,112,113,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 54 articles pertinent to associations between impaired internal working models and early parent-child relationships and offspring outcomes, 14,59,62,63,71,72,76,77,92,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][126][127][128][129][130]134,139,147,156,[165][166][167][168][169][170][171][172][173][174][175][176][177][178]…”
Section: Perinatal Substance Use and Impaired Internal Working Modelsmentioning
confidence: 99%